The Association Between Total Percent Fat and Serum Uric Acid in Adults - Sun, Juan; Yue, Chenyang; Liu, Zhen; Li, Jie; Kang, Weiming (Frontiers in Nutrition, 2022)
Background: Serum uric acid (SUA) has been proven to be closely associated with metabolic abnormalities, including obesity. This study aimed to investigate the detailed relationship between total percent fat (TPF) and SUA among adults. Methods: Briefly, 23715 adults aged 18 to 59 years in the National Health and Nutrition Examination Survey (NHANES) 1999-2018 were included in this study. Multivariable linear regression models were used to examine the association between TPF and SUA. Subgroup analyses stratified by sex were also performed by multivariable linear regression. Then, fitted smoothing curves and generalized additive models were also applied to address the nonlinear relationship between TPF and SUA. Finally, a recursive algorithm was used to calculate the inflection point in the nonlinear relationship and a two-piecewise linear regression model was used to analyze the relationship between TPF and SUA separately on both sides of the inflection point. Results: There were 15808 (66.7%) obese individuals in all 23715 participants. In the fully adjusted model, there was a positive association between TPF and SUA (β=1.20, 95% CI: 0.95-1.45), and this positive association was consistent in both males and females in the subgroup analysis stratified by sex in all three models. Besides, in males, the association of TPF and SUA was an inverted U-shaped curve (inflection point: 32.7%), while a linear relationship was observed in females. Conclusions: Our study revealed a significant positive relationship between TPF and SUA among adults and this association remained statistically significant when stratified by sex, but the shape of the smoothing curve in males differed from that in females.